1983
DOI: 10.1161/01.res.53.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane generation after thrombin. Protective effect of thromboxane synthetase inhibition on lung fluid balance.

Abstract: SUMMARY. We examined the role of thromboxane in mediating the alterations in pulmonary hemodynamics and in lung fluid and protein exchange after thrombin. Studies were made in control sheep and in sheep pretreated with the thromboxane synthetase inhibitor, Dazoxiben (injection of 10 mg/kg followed by infusion of 4 mg/kg per hr). Thrombin infusion caused an increase in mixed venous and aortic concentrations of thromboxane B2, a stable degradation product of thromboxane A2, whereas the concentrations of 6-keto-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…Garcia-Szabo et al 20 demonstrated that a selective inhibitor of thromboxane synthesis prevented the thrombin-induced increases in pulmonary lymph flow and the lymph protein clearance in intact sheep, suggesting that TxA 2 contributes to the increase in lung vascular permeability after thrombin infusion. However, while administration of arachidonic acid produced pulmonary venoconstriction associated with TxA 2 production in lungs, the microvascular permeability was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Szabo et al 20 demonstrated that a selective inhibitor of thromboxane synthesis prevented the thrombin-induced increases in pulmonary lymph flow and the lymph protein clearance in intact sheep, suggesting that TxA 2 contributes to the increase in lung vascular permeability after thrombin infusion. However, while administration of arachidonic acid produced pulmonary venoconstriction associated with TxA 2 production in lungs, the microvascular permeability was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is disagreement concerning the effect of TxA 2 on pulmonary microvascular permeability [10, 24,27]. Thromboxane synthetase inhibition prevents an increase in pulmonary vascular permeability in sheep after thrombin infusion [7] or after limb ischemia and reperfusion [8]. These findings suggest that T x A 2 contributes primarily to increased lung vascular permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The rise in mean pulmonary artery pressure after infusion of thrombin may probably be due to aprofound increase in pulmonary vascular resistance resulting from thrombin-induced release of thromboxane AZ (20,8). It is therefore conceivable that the improvement of the mean pulmonary artery pressure after thrombin infusion in the indomethacin group might be due mainly to inhibition of thromboxane synthesis resulting from cyclooxygenase inhibition, and consequently to a decrease in pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this assumption is mostly based on studies using various cyclooxygenase inhibitors. Among these arachidonate metabo-lites, thromboxane is known to be associated with sequences of events that follow infusion of thrombin in the rat (20), and with the development of thrombin-induced pulmonary edema in sheep (8,9). lncreased permeability to protein may also result from entrapment of fibrin (6) and leukocytes (2 1,s) in the lung.…”
Section: Introductionmentioning
confidence: 99%